Study of the interface - interphase of a Mg-CNT composite made by an alternative sandwich technique (2017)
Carbon nanotubes (CNTs) have been studied as potential reinforcement for Metal Matrix Composites (MMC) for improving the mechanical properties. However, dispersion and alignment of CNTs in the matrix has been very difficult due to their tendency to form clusters. In the present investigation, the synthesis of AZ31B magnesium alloy reinforced with multi-walled carbon nanotubes (MWCNTs) have been developed via the “sandwich” technique. This technique produces a material comprised of a metallic matrix and banded structures-layers of MWCNTs, where a polymeric solution is used to disperse and align the MWCNTs. As a result, a better dispersion and alignment of the CNTs in metal matrix composites was obtained. The results obtained showed a good interface between the metal matrix and the MWCNTs, allowing a very good interfacial bonding; thus, the mechanical properties, both at the nano level and in bulk, always showed a good behavior. For this characterization, several microscopy techniques including TEM in situ testing, nanomechanical tests and bulk mechanical tests were used. In the studied zones, interphases between the metal matrix and MWCNTs were not found, phases which could hamper the proper load transference between the matrix and reinforcement. HRTEM analysis allowed to identify the interactions between the metal matrix composites and MWCNTs. In the HRTEM images a semi-coherent and coherent interface between the metal matrix and MWCNTs was found. Additionally, two type of dislocations at the interface were identified: stacked and some dislocations formed to accommodate the Mg crystalline cell in order to produce a semi-coherent surface. No intermediate interphases were found in the studied zones. Notched micro-cantilever in situ TEM tests showed the dependency of the fracture toughness with the MWCNTs added in the magnesium matrix. Suggesting that the fracture toughness of the reinforced zone increases with the MWCNTs percentage added. This changes in the fracture toughness is due to the different strengthening mechanisms such as grain size, dislocation activity and finally to the reinforcements action. On the other hand, microtraction test of the composite clearly shown an increasing in the ultimate strength, stiffness and fracture toughness while the main final failure mechanism of the composite was delamination. Finally, PEO (plasma electrolytic oxidation) coatings were applied on the composite surfaces in order to protect them against corrosion. The results showed a good mechanical and electrochemical behavior of the coating. These results allow thinking in using this kind of composites in medical applications.